Strengthening national genebanks through genomics and regional collaboration: lessons from Latin America and the Caribbean - Carvajal‑Yepes, Monica; Petroli, Cesar; Correa, Miguel; Breseghello, Flavio; Salazar, E.; Chassaigne Ricciulli, Alberto Antonio; Reyes-Herrera, Paula Helena; Guzman, Manuel; Mendoza, Amalio; Vidal, Rafael; Condón, Federico; De Almeida Silva, Natália Carolina; et al. (Elsevier, 2026)
Latin America and the Caribbean (LAC) is a center of origin and domestication for globally important crops such as cassava, common bean, maize, and potato, all of which are key to food and nutrition security worldwide. Despite this strategic role, many national genebanks in the region face technical, financial, and policy barriers that limit the use of genomic tools for characterization and conservation. These genebanks safeguard the genetic diversity needed to enhance crop yields, climate-change resilience, nutritional quality, and pest and disease resistance. In 2022, CGIAR Centers and partners established the "Community of Practice (CoP) of national genebanks in LAC" to strengthen regional capacity for generating and interpreting digital sequence information (DSI), facilitate collaboration, and promote sustainable management of plant genetic resources. Through coordinated capacity-building activities, joint crop-based analyses, and shared learning, the CoP has connected 17 institutions across 13 countries. Members have begun generating and interpreting DSI for common bean, maize, and potato, while addressing gaps in data sharing, interoperability, and policy frameworks. Looking ahead, the CoP seeks to conduct diversity analysis, establish regional core collections, integrate existing global data portals, and advocate for policy alignment to sustain genomic characterization and access to diversity. This CoP initiative provides a model applicable in other regions to strengthen genebank operations through collaborative innovation and coordinated action, contributing to resilient and equitable global food systems.